The different potential of sponge bacterial symbionts in N₂ release indicated by the phylogenetic diversity and abundance analyses of denitrification genes, nirK and nosZ. - Xia Zhang (Public Library of Science (PLoS), 2013)
Nitrogen cycle is a critical biogeochemical process of the oceans. The nitrogen fixation by sponge cyanobacteria was early observed. Until recently, sponges were found to be able to release nitrogen gas. However the gene-level evidence for the role of bacterial symbionts from different species sponges in nitrogen gas release is limited. And meanwhile, the quanitative analysis of nitrogen cycle-related genes of sponge microbial symbionts is relatively lacking. The nirK gene encoding nitrite reductase which catalyzes soluble nitrite into gas NO and nosZ gene encoding nitrous oxide reductase which catalyzes N₂O into N₂ are two key functional genes in the complete denitrification pathway. In this study, using nirK and nosZ genes as markers, the potential of bacterial symbionts in six species of sponges in the release of N2 was investigated by phylogenetic analysis and real-time qPCR. As a result, totally, 2 OTUs of nirK and 5 OTUs of nosZ genes were detected by gene library-based saturated sequencing. Difference phylogenetic diversity of nirK and nosZ genes were observed at OTU level in sponges. Meanwhile, real-time qPCR analysis showed that Xestospongia testudinaria had the highest abundance of nosZ gene, while Cinachyrella sp. had the greatest abundance of nirK gene. Phylogenetic analysis showed that the nirK and nosZ genes were probably of Alpha-, Beta-, and Gammaproteobacteria origin. The results from this study suggest that the denitrification potential of bacteria varies among sponges because of the different phylogenetic diversity and relative abundance of nosZ and nirK genes in sponges. Totally, both the qualitative and quantitative analyses of nirK and nosZ genes indicated the different potential of sponge bacterial symbionts in the release of nitrogen gas.